Buy coal! Deposit markets prevent carbon leakage - Bård Harstad (Center for Economic Studies and ifo Institute (CESifo), 2010)
If a coalition of countries implements climate policies, nonparticipants tend to consume more, pollute more, and invest too little in renewable energy sources. In response, the coalition's equilibrium policy distorts trade and it is not time consistent. By adding a market for the right to exploit fossil fuel deposits, I show that these problems vanish and the first best is implemented. When the market for deposits clears, the coalition relies entirely on supply-side policies, which is simple to implement in practice. The result illustrates that efficiency can be obtained without Coasian negotiations ex post, if key inputs are tradable ex ante.
Keywords: Q54; Q58; H23; F55; 330; Coase; climate change; carbon leakage; supply vs. demand side policies; trade policies; the green paradox; environmental agreements; Klimaschutz; Internationale Umweltpolitik; Industrieverlagerung; Fossiler Energieträger; Erdölkonzession; Emissionshandel; Internationale Handelspolitik; Zeitkonsistenz; Theorie